Thiamine synthesis regulates the fermentation mechanisms in the fungus Aspergillus nidulans. Issue 9 (1st September 2016) - Shimizu, Motoyuki; Masuo, Shunsuke; Itoh, Eriko; Zhou, Shengmin; Kato, Masashi; Takaya, Naoki
Abstract: Thiamine pyrophosphate (TPP) is a critical cofactor and its biosynthesis is under the control of TPP availability. Here we disrupted a predicted thiA gene of the fungus Aspergillus nidulans and demonstrated that it is essential for synthesizing cellular thiamine. The thiamine riboswitch is a post-transcriptional mechanism for TPP to repress gene expression and it is located on A. nidulans thiA pre-messenger RNA. The thiA riboswitch was not fully derepressed under thiamine-limited conditions, and fully derepressed under environmental stressors. Upon exposure to hypoxic stress, the fungus accumulated more ThiA and NmtA proteins, and more thiamine than under aerobic conditions. The thiA gene was required for the fungus to upregulate hypoxic branched-chain amino acids and ethanol fermentation that involve enzymes containing TPP. These findings indicate that hypoxia modulates thiA expression through the thiamine riboswitch, and alters cellular fermentation mechanisms by regulating the activity of the TPP enzymes. Graphical abstract: : Upon exposure to hypoxic stress (B; –O2 ), the fungus accumulated more ThiA and NmtA proteins that involve in thiamine biosynthesis (A), and more thiamine than under aerobic conditions (B;+O2 ).